EDTA-induced pseudothrombocytopenia in association with bladder cancer. (20th June 2014) - Sahin, Cem; Kırlı, Ismail; Sozen, Hamdi; Canbek, Tugba Dibektas
Abstract : Pseudothrombocytopenia is the detection of low platelet counts by an autoanalyser despite lack of shortage in platelets. EDTA-induced pseudothrombocytopenia, the most frequently seen form in clinical practice, occurs mainly due to reaction of antiplatelet antibodies. Pseudothrombocytopenia is not only seen in healthy individuals but it is also reported in association with autoimmune, cardiovascular and liver parenchyma diseases and malignancy. We aimed to review approaches to pseudothrombocytopenia by presenting a case in which EDTA-dependent thrombocytopenia in association with bladder tumour was detected during examination for haematuria.